Interference of a neutrophil recruitment inhibitory factor upon the accumulation of inflammatory cells and airway hyperreactivity in sensitized guinea-pigs after intranasal antigen challenge. - Tavares-Murta, B. M. (1993)
1. A neutrophil recruitment inhibitory factor (NRIF) recovered from the crude supernatant of lipopolysaccharide (LPS)-stimulated macrophages inhibited neutrophil migration following both intratracheal and intravenous administration of LPS, but did not alter the pattern of leukopenia/leucocytosis induced by intravenous LPS. 2. The correlation between airway infiltration by inflammatory cells and hyperreactivity in lungs from actively sensitized and challenged guinea-pigs was investigated by use of NRIF. 3. Increased eosinophil counts were found in the bronchoalveolar lavage fluid from guinea-pigs sensitized with 10 micrograms ovalbumin and challenged at day 14 by the intranasal administration of the antigen. The increase was evident 5 h after challenge and persisted at 24 h. Neutrophil numbers were also increased at this time. Pretreatment with NRIF suppressed the leucocyte increase in the bronchoalveolar lavage fluid. 4. Bronchoconstriction and histamine release induced by 3 ng PAF injected into the isolated lungs were increased in challenged guinea-pigs as compared to sensitized but unchallenged controls. Pretreatment of the animals with NRIF did not interfere with this response, but significantly reduced the bronchoconstriction induced by ovalbumin injection. 5. Even though the increased number of inflammatory cells in bronchoalveolar lavage and airway hyperresponsiveness were concomitant, NRIF inhibited cellular infiltration but failed to alter airway hyperreactivity to PAF, demonstrating that these events may occur independently. Conversely, the inhibition of antigen-induced bronchoconstriction by NRIF suggests that this response is dependent upon the emigration of granulocytes.